ADOLESCENT EMOTIONS AND SKINCARE TEXTURE: A MIXED-METHODS EXPLORATORY STUDY - Agyl Muhammad Dzikrullah; Desi Setiyadi; Deby Puspitaningrum; Ira Siti Rohmah Maulida; Kana Safrina Rouzi (LP2M IAI Al-Khairat Pamekasan, 2025)
This study explores the effect of skincare product texture on users’ emotional responses, especially female adolescents aged 16–21 years. Using mixed-method, quantitative and qualitative approach, this study is conducted in Jakarta, Tangerang, Bandung, Banyumas, and Yogyakarta. Total of 30 participants in this study follow three stages of product use: First Touch, During Application, and After-Absorption. Participants’ emotions are measured using the Self-Assessment Manikin (SAM) for the dimensions of valence, arousal, and dominance, and also the PANAS scale to measure changes in positive and negative emotions before and after using the skincare product. The result shows that at the First Touch stage, there is no significant difference in emotions statistically. However, qualitative data reveal variations in perceptions of sticky or runny texture. At the During Application stage, softness shows a significant effect on the sense of control and positive emotions. Meanwhile, at the After-Absorption stage, stickiness, greasiness, and film residue have a significant effect. Product with a soft texture, fast absorption, and no residue (product 2) is the most preferred and show to significantly reduce negative emotions based on the PANAS scale. This study emphasizes the importance of considering texture in skincare product development, as sensory experiences play a role in shaping user emotions. Further research is recommended to explore ingredients such as humectants and occlusives, as well as using physiological tools such as facial coding or EEG to gain a more objective understanding.